Analysis Of Student’s Reflective Thinking Ability In Solving PISA Based Mathematic Problems Of SPLDV Based on Critical Thinking Skills - Asih, Erviani Agustyaning; Pramasdyahsari, Agnita Siska Pramasdyahsari; Aini, Aurora Nur (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
SPLDV is one of the materials that corresponds to aspects of reflective thinking skills where students are required to be able to solve problems according to the understanding and concept of reflective thinking. So that students' reflective thinking skills become an important thing in solving SPLDV problems. Meanwhile, the ability to think reflectively can be honed by solving PISA-based questions by paying attention to the steps for solving them. This study aims to determine students' reflective thinking skills in solving PISA-based math problems in SPLDV material for students with critical thinking abilities. This research is a qualitative descriptive study. The subjects of this research were class VIII A students of SMP Negeri 10 Semarang consisting of 3 students, 1 student with high critical thinking ability, 1 student with moderate critical thinking ability, and 1 student with low critical thinking ability. The selection of subjects was based on the results of critical thinking skills tests on the SPLDV material. Data collection techniques used in this study were tests, interviews and documentation. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. Techniques for checking the validity of the data using the triangulation method. The results of this study indicate that students with high critical thinking skills can fulfill 4 indicators of reflective thinking skills. Students with moderate critical thinking skills can fulfill 3 indicators of reflective thinking skills. Meanwhile, students with low critical thinking skills meet 2 indicators of reflective thinking skills.